Analisis Efektivitas Program Keluarga Harapan (PKH) di Desa Malenge Kabupaten Tojo Una-Una - Nurhaniva Nurhaniva; Khairunisa Kahar; Ainun Lestari (Journal of Innovative and Creativity, 2025)
This study investigates the effectiveness of the Family Hope Program (Program Keluarga Harapan/PKH) in Malenge Village, Tojo Una-Una Regency, Indonesia, using a qualitative case study approach and a Logic Model evaluation framework. Malenge, characterized by remote geography and a high poverty rate, poses significant operational challenges for cash transfer programs. Despite strong coordination among local stakeholders and adequate beneficiary understanding, PKH implementation faces structural constraints, notably unstable digital infrastructure and extreme weather, which delay fund disbursement and increase compliance costs. Results demonstrate that, while PKH effectively enhances school attendance and education expenditure in the short term, much of the aid is diverted to subsistence needs due to acute poverty, creating a substitution effect. This finding redefines success in terms of process quality rather than outcome fidelity. The study emphasizes the need for adaptive policy interventions that integrate subsistence support and address logistical and digital exclusion challenges to optimize PKH impact in isolated regions.